(untitled) (Mayéutica Revista Científica de Humanidades y Artes, 2022)
A pictorial exhibition of the work of Andrés Barrios Gallipoli, entitled La mirada orgánica, was recently inaugurated at the Exhibition Hall of the Metropolitan University, Unimet, Caracas, under the auspices of the Culture Department and the visual proposal of Ricardo Arispe. Andrés Barrios Gallipoli, is a "renaissance man" in the strictest sense of the expression, who has creatively moved through literature, the plastic arts and stage performance, with a fundamental emphasis on music, obtaining important recognitions in his different facets due to his creative quality. On this occasion, some of the works contained in the aforementioned exhibition are included as a partial extension of the hall and selected by the author.